2019
DOI: 10.1053/j.gastro.2019.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome Signatures Associated With Steatohepatitis and Moderate to Severe Fibrosis in Children With Nonalcoholic Fatty Liver Disease

Abstract: This article has an accompanying continuing medical education activity, also eligible for MOC credit, on page e18 (https:// www.gastrojournal.org/cme/home). Learning Objective: Upon completion of this CME activity, successful learners will be able to explain measures of disease severity in children with nonalcoholic fatty liver disease (NAFLD) and identify factors in the intestinal microbiome that associate with disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
167
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(209 citation statements)
references
References 55 publications
15
167
3
3
Order By: Relevance
“…Moreover, the authors found an elevated production of secondary bile acids from CRC metagenomes, suggesting a metabolic link between cancer-associated gut microbes and a fat-and meat-rich diet. In line with other studies showing gut microbiome signatures driven by specific diseases [160,161], Wirbel et al established CRC-specific microbiome signatures distinct from other conditions such as type 2 diabetes, Parkinson's disease, and inflammatory bowel disease. Notably, the gut microbiome of CRC cases showed a higher diversity as compared to controls, which was explained by the translocation of microbes from the oral cavity into the colon.…”
Section: Consequences Of Altered Intestinal Homeostasis: Correlationsupporting
confidence: 76%
“…Moreover, the authors found an elevated production of secondary bile acids from CRC metagenomes, suggesting a metabolic link between cancer-associated gut microbes and a fat-and meat-rich diet. In line with other studies showing gut microbiome signatures driven by specific diseases [160,161], Wirbel et al established CRC-specific microbiome signatures distinct from other conditions such as type 2 diabetes, Parkinson's disease, and inflammatory bowel disease. Notably, the gut microbiome of CRC cases showed a higher diversity as compared to controls, which was explained by the translocation of microbes from the oral cavity into the colon.…”
Section: Consequences Of Altered Intestinal Homeostasis: Correlationsupporting
confidence: 76%
“…Therefore, studies that have compared individuals with biopsy-proven NASH to a no-biopsy obese control group might have been biased by un-diagnosed NASH among the controls. Currently, there are few studies with biopsy-proven NAFL or NASH [15][16][17][18], and only one study was conducted with biopsy-proven healthy individuals [15]. Therefore, the present study has a homogeneous, well characterized and correctly diagnosed population by biopsy-proven NAFL patients, NASH patients, and healthy individuals in Asia that gives value to the results.…”
Section: Discussionmentioning
confidence: 93%
“…Animal experiments in which the microbiome has been manipulated have shown that the gut microbiota plays an important role in the pathogenesis of NAFLD [13,14]. Nevertheless, only a few studies have linked gut dysbiosis with the severity of NAFLD in humans [15][16][17][18]. These studies had small sample sizes, heterogeneous populations, and divergent tools for gut microbiota analysis.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing reports that the intestinal microbiome plays an important role in the pathogenesis of NAFLD. Animal models and human volunteer clinical studies have provided considerable information on the association between dysbiosis and NAFLD pathogenesis 57‐60 . However, less is known about the mechanisms involved in the bidirectional liver‐gut microbiome axis and how dysbiosis in the gastrointestinal tract contributes to the incidence of NAFLD.…”
Section: Discussionmentioning
confidence: 99%